2015
DOI: 10.1097/bot.0000000000000366
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Vitamin D Therapy in Orthopaedic Trauma Patients

Abstract: Vitamin D therapy improved the majority of the patients' vitamin D-25-OH level but did not normalize most. Patients with initial deficiency had the largest improvement. This study indicates that vigilance is required to adequately treat a low serum vitamin D-25-OH level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
0
13
0
5
Order By: Relevance
“…Robertson et al conducted study on 201 adult trauma patient with vitamin D deficiency. After supplementation 80% of them improved [24] . 60 deficient patients were randomized in two groups and one group was given weekly followed by daily dosing, while other was given only daily regime.…”
Section: Discussionmentioning
confidence: 97%
“…Robertson et al conducted study on 201 adult trauma patient with vitamin D deficiency. After supplementation 80% of them improved [24] . 60 deficient patients were randomized in two groups and one group was given weekly followed by daily dosing, while other was given only daily regime.…”
Section: Discussionmentioning
confidence: 97%
“…population. [23][24][25] Naturally, the increase in serum levels is dependent on patient adherence, which also seems to vary between populations. Andres et al reported 82% of their adult fracture patients were adherent to a daily 1,600 IU vitamin D dose; 25 this is much higher than the 33% of participants that reported taking their supplement daily in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It is estimated that 65% of Canadians and 77% of Americans have hypovitaminosis D. 3,4 Previous fracture care research has focused on vitamin D levels in elderly populations 5,6 ; however, recent research has found that more than two-thirds of nongeriatric fracture patients may have serum vitamin D levels that are too low to maintain adequate bone health. [7][8][9][10][11] Although it is well established that vitamin D plays an important role in bone metabolism, its role in acute fracture healing is less clear. Experimental studies in animals [12][13][14][15][16] have suggested that vitamin D may have a positive impact on fracture healing; however, a systematic review of fracture healing in humans concluded that the influence of vitamin D deficiency on fracture outcomes is unknown and there is limited evidence available to guide practice.…”
Section: Introductionmentioning
confidence: 99%